2019
DOI: 10.1093/ejo/cjz088
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effectiveness of a tailored mobile application in increasing the duration of wear of thermoplastic retainers: a randomized controlled trial

Abstract: Summary Background The ‘My Retainers’ mobile application is a patient-informed intervention designed to enhance removable retainer wear and associated patient experiences during the retention phase. Objectives To evaluate the effect of receiving the ‘My Retainers’ application on objectively assessed thermoplastic retainer (TPR) wear time, stability, periodontal outcomes, patient experiences, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 38 publications
1
16
0
8
Order By: Relevance
“… 19 , 20 In the past few years, the market has assisted an increased availability of orthodontic apps to enhance long-distance monitoring and compliance, 21 and a recent study confirmed the positive attitude of patients towards this new digital technology. 22 In orthodontics, it can be applied for monitoring of several treatment aspects, 23 including patients’ oral hygiene during the therapy, 16 , 24 , 25 treatment with clear aligners, 26 , 27 rapid palatal expansion, 15 , 28 , 29 adherence to the use of removable retainers, 8 active working time of self-ligating straight-wire appliances, 30 and clinical follow-up of corticotomy-accelerated orthodontic therapies. 31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 , 20 In the past few years, the market has assisted an increased availability of orthodontic apps to enhance long-distance monitoring and compliance, 21 and a recent study confirmed the positive attitude of patients towards this new digital technology. 22 In orthodontics, it can be applied for monitoring of several treatment aspects, 23 including patients’ oral hygiene during the therapy, 16 , 24 , 25 treatment with clear aligners, 26 , 27 rapid palatal expansion, 15 , 28 , 29 adherence to the use of removable retainers, 8 active working time of self-ligating straight-wire appliances, 30 and clinical follow-up of corticotomy-accelerated orthodontic therapies. 31 …”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, several remote systems have been developed in the last decade, including the embedding of a microsensor into the acrylic of the appliance to record temperature, such as the Smart Retainer (Scientific Compliance, Atlanta, GA, USA) 4 and TheraMon Sensor (Handelsagentur Gschladt, Hargelsberg, Austria). 5 Other studies on mobile applications providing active reminders 6 - 8 suggest that regular control of patients by the orthodontist can positively influence patient compliance. 9…”
Section: Introductionmentioning
confidence: 99%
“…A mobile retainer reminder app was developed to improve adherence to retainers; however, it did not seem to significantly improve objectively assessed adherence levels, stability or patient experiences at three-month follow-up. 21 With conventional mobile reminder apps, tracking is dependent on patients entering the usage data themselves and some users perceived this as a 'commitment' and 'time-consuming' . 22 To overcome this issue, another pilot study coupling Bluetooth tracking with reminders has shown that this type of compliance tracking has a clinically acceptable level of accuracy and usability, validating its use within future clinical studies.…”
Section: Monitoring Retentionmentioning
confidence: 99%
“…6 Microsensors have demonstrated that patients wear their retention appliances for a shorter time per day than is recommended. [7][8][9][10][11][12][13] The published data regarding stability are based on subjective wear-time measures such as patient and parent reports or estimates of orthodontists. [14][15][16][17][18][19][20][21][22][23] Although wear data are subjective, part-time retainer wear (8-12 h/d) is reported to be as beneficial as fulltime wear in preserving treatment results.…”
Section: Introductionmentioning
confidence: 99%
“…15,17,22 Only one previous study assessed stability outcomes with objectively measured retainer wear. 13 However, the question of whether short wear times (SWTs) or long wear times (LWTs) are effective for the maintenance of stability remains questionable. Therefore, the aim of this study was to determine how the amount of objectively measured retainer wear affects posttreatment stability.…”
Section: Introductionmentioning
confidence: 99%